Pengaruh Citra Sekolah Dan Lokasi Terhadap Keputusan Memilih MTs Swasta â€œXâ€ Kota Pekanbaru - Ansori, Putra Budi (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted at Privat MTs â€œXâ€, Pekanbaru City in 2023. The aim of this research is to determine the influence of School Image (X1) and Location (X2) on Choosing Decisions (Y) at Privat MTs â€œXâ€, Pekanbaru City. Because the image of the school and location can influence the decision to choose a school. The population in this study was 579 who chose schools at Privat MTs â€œXâ€ Pekanbaru City, then based on the help of the Slovin formula the research sample was 86 respondents. The sampling technique was carried out by purposive sampling. The research results showed that: first, the results of the F test concluded that jointly/simultaneously the variables School Image (X1) and Location (X2) influenced the decision to choose Privat MTs â€œXâ€ Pekanbaru City. Second, partially, the School Image variable (X1) has an influence on the decision to choose Privat MTs â€œXâ€ Pekanbaru City and is proven to have a positive and significant effect. Third, partially, the location variable (X2) has a positive and significant effect on the decision to choose Privat MTs â€œXâ€ Pekanbaru City. Fourth, the contribution of the influence of the School Image and Location variables to changes in the Decision to choose variable is 41.4%. while the remaining 58.6% was influenced by other variables not examined in the research